Toward an Invitational Andragogy: Articulating a Teaching Philosophy for the Andragogic Classroom - Whitney Tipton; Stephanie Wideman (Central States Communication Association, 2021)
Students older than 25 years are a growing population on our campuses. However, separating these students and labeling them as "nontraditional" further isolates them from campuses that are already geared toward younger learners. This reflective essay explains the need for a philosophy of invitational andragogy-a classroom approach rooted in invitational rhetoric (S. Foss & Griffin, 1995) and Knowles's assumptions about older learners (1980, 1984). While inviting transformation is important in all classrooms, it is especially important for older learners who often feel separated from the campus at large. To explain how an invitational approach to the andragogic classroom can be achieved, we identify opportunities to apply the strategic prongs of invitational rhetoric: (a) offering perspectives and (b) creating external conditions that promote safety, value, and freedom.